PSEUDORHABDOMESON - A NEW GENUS OF CARBONIFEROUS BRYOZOANS: MORPHOLOGY AND ASTOGENY - Gorjunova R.V. (My University, 2002)
A new genus, Pseudorhabdomeson, with its type species, Ps. polygonium sp. nov., from the Kasimovian of the Russian Platform is described. Its axial zooecium has a distinctive form of a prismatic tube with a polygonal cross section. Using this genus as an example, the astogeny of rhabdomesids is for the first time represented by the zones of astogenetic change and astogenetic repetition. In addition to Ps. polygonium, this genus includes nine other species, which previously were assigned to Rhabdomeson, from the Carboniferous of Russia, Ukraine, and the United States.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная